Energetic pathways and influence of the metallacyclobutane intermediates formed during isobutene/2-butene cross-metathesis over WH3/Al2O3 supported catalyst12. Issue 10 (14th March 2016) - Motta, A.; Szeto, K. C.; Taoufik, M.; Nicholas, C. P.
Abstract : The preferred catalytic cycle occurring in the conversion of isobutene and 2-butene to propylene and pentenes over WH3 /Al2 O3 has been investigated via an energetic analysis of the metallacyclobutanes formed upon 2 + 2 butene cycloaddition with alumina supported tungsten alkylidenes. Abstract : The preferred catalytic cycle occurring in the conversion of isobutene and 2-butene to propylene and pentenes over WH3 /Al2 O3 has been investigated via an energetic analysis of the metallacyclobutanes formed upon 2 + 2 butene cycloaddition with alumina supported tungsten alkylidenes. Within the metallacyclobutanes investigated, steric destabilization generally increased as the substituents increased from ethyl (from 1-butene) to vicinal dimethyl (from 2-butene) to geminal dimethyl (from isobutene). The relative stabilization of the metallacyclobutanes is also affected by the steric interaction between the metallacyclobutane substituents and either the surface or W–H ligand. The catalytic cycle involving surface intermediates2c (ethylidene) and2d (methylidene) is shown to be the most important in the reaction pathway with the analysis also showing that the system feeds back to ethylidene intermediate2c after non-preferred butene cycloadditions which yield propylidenes2a or2b . Moreover, we show that2c and2b are involved in the preferred cycle for formation of 2-pentene minor products, while2d and2b are involved in the preferred cycle for the formation of 3-hexene minor products.